Optical Coherence Tomography Findings of Underlying Choroidal Neovascularization in Punctate Inner Choroidopathy - Agarwal, Aniruddha; Handa, Sabia; Marchese, Alessandro; Parrulli, Salvatore; Invernizzi, Alessandro; Erckens, Roel J.; Berendschot, Tos T. J. M.; Webers, C. A. B.; Bansal, Reema; Gupta, Vishali (Frontiers in Medicine, 2021)
Purpose: To analyze findings on optical coherence tomography (OCT) suggestive of choroidal neovascularization (CNV) in lesions of punctate inner choroidopathy (PIC). Methods: In this multi-center retrospective study, clinical data of patients with PIC were retrospectively analyzed. Quantitative data (height, width, and volume of PIC lesions), and qualitative data (disruption of ellipsoid zone (EZ)/Bruch’s membrane (BM), outer retinal fuzziness, and choroidal back-shadowing) were compared between CNV+ and CNV- groups using Mann-Whitney U and Fischer’s exact test. Results: Thirty-five eyes (29 patients; 21 females; mean age: 33.3±6.5 years) were selected for analysis. Of the 35 PIC lesions studied, 17 had underlying CNV. Lesions with CNV+ had larger height, width, and volume (p<0.001) and several distinctive features like disruption of EZ and BM, outer retinal fuzziness, and hypo-reflective back-shadowing (p<0.001) compared to CNV- lesions. Conclusions: Quantitative and qualitative OCT analysis can aid in the prediction of an underlying CNV in eyes with PIC.